Size Matters: Rethinking of the Sizing Classification of Pituitary Adenomas Based on the Rates of Surgery: A Multi-institutional Retrospective Study of 29,651 Patients - Bhimani, Abhiraj D.; Schupper, Alexander J.; Arnone, Gregory D.; Chada, Deeksha; Chaker, Anisse N.; Mohammadi, Nicki; Hadjipanayis, Costas G.; Mehta, Ankit I. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Pituitary adenomas are historically classified into microadenoma or macroadenomas based on size less than or greater than/equal to 1c m. “Giant” adenomas describe tumors ≥4 cm. The aim of this study is to present an evidence-based approach to size classification based on national trends.Design The design involved is multi-institutional retrospective study.Participants A total of 29,651 patients were studied from National Cancer Institute's SEER program from 2004 to 2016 across the United States.Main Outcome Measures The main outcome measures include demographics, treatment characteristics, and overall survival in the population.Results At the 20-mm threshold, the likelihood of operation exceeds the likelihood of nonoperative management. Patients with adenoma size 1 to 19 mm had significantly longer overall survival compared with 20 to 50 mm (Log rank: p < 0.0001). No survival difference was found between size 20 to 29 mm and larger. There was no significant difference in the rate of surgery between 30 to 39 mm and 40 to 50 mm tumors(p = 0.5035). Surgery group had a higher overall survival compared with nonsurgically managed patients (Log rank: p < 0.0001).Conclusion Microadenoma has classically been used to describe pituitary tumors less than 1 cm, though no clinical significance of this threshold has been demonstrated. The current study suggests a size cut-off of 20 or 30 mm as more clinically relevant. Still, future studies are warranted to examine the significance of this classification by specific tumor type, and subclassified as appropriate. There is no difference in the rate of surgery or survival for adenomas between 30 and 50 mm, challenging the 4-mm cutoff threshold for “giant” adenoma.
Keywords: pituitary adenoma; giant adenoma; macroadenoma; microadenoma; surgery; SEER